Infección del sitio quirúrgico en pacientes con Diabetes tipo 2 sometidos a cirugía ortopédica - García Rodríguez, Tatiana Lizseth (2022)
To determine if diabetes mellitus type 2 (DM2) is a risk factor for surgical site infections (SSI) in patients underwent orthopedic surgeries. Materials and Methods: A retrospective cohort study was conducted. The medical histories of patients who underwent to open reduction and internal fixation for humerus, radius, ulna, femur, tibial or fibula fracture at two centers “Hospital Regional Docente de Trujillo” and “Hospital Belen” between February 2017 and February 2020 were reviewed. Results: A total of 340 medical histories were review, including 73 (21.5%) DM2 patients and 267 (78.5%) non DM2 patients. The relative risk of SSI in diabetics was 3.01 (CI: 95% 1.50-6.07, p< 0.005). The patients who develop SSI were 39 (11.5%), and 7 (17.9%) had DM2. Age, gender, weight, pre-prandial glucose, location of the fracture, preoperative stay, operation duration, ASA and anesthesia type were not identified as risk factors associated with SSI. Conclusions: The incidence of SSI was 30.4% in diabetic patients and 10.1% in non-diabetic. Diabetics have three times the risk of SSI than non-diabetics. Furthermore, the DM2 is an independent risk factor for SSI.